3. Elige el procedimiento correcto para resolver la siguiente ecuación: (x-2)
A 3(x - 2) = -4(-x - 2)
3x - 6 = 4x + 8
3x - 4x = 8 + 6
-X = 14
(-1)(-x) = (-1)(14)
X = -14
B 3(x - 2) = -4(-x + 2)
3x - 6 = 4x - 8
3x - 4x = -8 + 6
-X=2
(-1)(-x) = (-1)(2)
x = -2
Reforzano
digital ciclo 20-21
C 3(x - 2) = -4(-x + 2)
3x - 6 = 4x - 8
3x - 4x = -8 -6
-X = -14
(-1)(-x) = (-1)(-14)
X= 14
D 3(x - 2) = -4(-x + 2)
3x - 6 = 4x - 8
3x - 4x = -8 + 6
-X = -2
(-1)(-x) = (-1)(2)
X=2
2
Adjuntos:
![](https://es-static.z-dn.net/files/d73/6377b60a230b839e899ec60f4035ac9f.jpg)
Respuestas
Respuesta dada por:
2
Explicación paso a paso:
jajajajajsjqcevwkqvwvs show
wvwhwk2vwiegeisv28wvww
Adjuntos:
![](https://es-static.z-dn.net/files/db1/49fb793fbf95e1d34f4457a433030ca7.jpg)
Preguntas similares
hace 2 años
hace 2 años
hace 5 años
hace 5 años
hace 5 años
hace 7 años
hace 7 años
hace 7 años